Evaluation of the germicidal action of ultraviolet light in biosafety cabinet concerning bacterial species - Barbosa, Adriana Sierra Assencio Almeida [UNESP]; de Camargo, Mariana Priscila; de Magalhães Tavares Moreira, Julie Anne Corrêa; Diman, Rafael Balan [UNESP]; da Silveira, Mônica [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
Introduction: The biological safety cabinet (BSC) is a collective protective device used to hold aerosols produced in laboratory procedures. The BSC protects workers, material handling, and the environment. It relies on ultraviolet light (UV) lamps that have germicidal action, altering the nucleic acids of microorganisms. Objective: The objective of the present study was to evaluate the germicidal action of BSC class II type A2 UV light against the culture of two bacterial species with different conditions of exposure to UV light. Methods: For the research, the bacteria Staphylococcus aureus ATCC 25923 and Klebsiella pneumoniae ATCC 10031 were used, at a concentration of 1.5x108 Colony Forming Units/ml (CFU/ml), which were seeded in Petri biplates. Use UV light under different conditions and times. Results: The bacterial species showed the same growth or inhibition profile when subjected to different exposure conditions. Petri dishes with the cover open and protected or not with sterilization packaging showed bacterial inhibition at 15 and 20 minutes. The microorganisms in the biplates protected by the aluminum foil and in the biplates with the cover on, regardless of the time and condition, showed bacterial growth. Conclusion: With the results obtained, it is suggested that the germicidal action of UV light was effective, ensuring adequate decontamination and ensuring quality in laboratory biosafety.
Avaliação da ação germicida da luz ultravioleta de cabine de segurança biológica frente às espécies bacterianas
Keywords: Biosafety cabinet; Klebsiella pneumoniae; Staphylococcus aureus; UV light